2017
DOI: 10.1200/jco.2016.68.6394
|View full text |Cite
|
Sign up to set email alerts
|

Early Positron Emission Tomography Response–Adapted Treatment in Stage I and II Hodgkin Lymphoma: Final Results of the Randomized EORTC/LYSA/FIL H10 Trial

Abstract: Purpose Patients who receive combined modality treatment for stage I and II Hodgkin lymphoma (HL) have an excellent outcome. Early response evaluation with positron emission tomography (PET) scan may improve selection of patients who need reduced or more intensive treatments. Methods We performed a randomized trial to evaluate treatment adaptation on the basis of early PET (ePET) after two cycles of doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) in previously untreated-according to European Organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
393
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(418 citation statements)
references
References 19 publications
10
393
1
14
Order By: Relevance
“…Interim analysis of the H10 study (Raemaekers et al , ) demonstrated a superior PFS for patients receiving involved‐nodal RT (INRT). In recently published final results, no significant difference in PFS was demonstrated between patients with EUF‐HL and negative PET‐2 who did or did not receive INRT (HR 1·45 95% CI 0·84–2·5) (André, ). The non‐inferiority of the results observed in the arm not receiving INRT was refuted due to the broad 95% CI.…”
Section: Discussionmentioning
confidence: 97%
“…Interim analysis of the H10 study (Raemaekers et al , ) demonstrated a superior PFS for patients receiving involved‐nodal RT (INRT). In recently published final results, no significant difference in PFS was demonstrated between patients with EUF‐HL and negative PET‐2 who did or did not receive INRT (HR 1·45 95% CI 0·84–2·5) (André, ). The non‐inferiority of the results observed in the arm not receiving INRT was refuted due to the broad 95% CI.…”
Section: Discussionmentioning
confidence: 97%
“…For each patient, PET0, PET2, and PET4 images were sent within 24 hours to 3 central panel PET experts (M.M., A.B.-R., or S.B.). PET2 and PET4 were binary interpreted as positive or negative, as per international harmonization project (IHP) criteria, 14 with the previously published precision 13,15,16 : the "clearly increased activity relative to the reference background," which defines positive residual uptake in the IHP criteria, should be at least 25% higher than this background. A central review was performed within 72 hours of receiving PET2 images, and the final result was sent back to the investigator to allow planning of stem cell harvest after cycle 3 in case of positive PET2.…”
Section: Lnh2007-3b Study Designmentioning
confidence: 99%
“…The 3-y progression-free survival (PFS) was 97.1% for patients receiving involved-field radiotherapy versus 90.8% for no further treatment in a perprotocol analysis (hazard ratio [HR], 2.36; 95% confidence interval [CI], 1.13 to 4.95; P 5 0.02). Similar results were reported in the H10 trial; patients who were in CMR after 2 cycles of ABVD were randomized using a PET-driven schema to either standard therapy (3-4 cycles of ABVD followed by involved-node radiotherapy, for favorable and unfavorable disease, respectively) or 4-6 cycles of ABVD alone (for favorable and unfavorable disease, respectively) (6 [unfavorable]; P 5 0.03). Combined-modality therapy thus resulted in a small improvement in disease control in both trials, although the high PFS and lack of effect on overall survival (OS) suggest that many patients may be cured using chemotherapy alone.…”
Section: Hl Deescalation Strategiesmentioning
confidence: 67%